Dialectal Words of Village Struhantsi as an Object of Lexicographical Processing: K.5 (КРОВ – КЬИЯ́Х) (Linguostylistic Studies, 2016)
The article offers new approaches to the lexicographical word processing. The object of the study is the village Stryhantsi (Tysmenets district, IvanoFrankivsk region) dialectal peculiarities. This dialect is spoken with some specifics by the residents in the south-west of Naddnistrianshchyna. The bulk of the dictionary word stock, represented by appellative lexicon, is supplemented with a number of onyms (surnames, street nicknames, microtoponyms). Colloquial expressions are included into the dictionary alongside with the idiomatic ones. The article presents the fifth part of the selected lexicon – words that begin with the letter K (КРОВ – КЬИЯ́Х). Each dictionary entry lists all the lexeme meanings known to the authors, particularly those used in the meaning which is different from the literary variant. Some of the lexemes are of great interest for the researchers of the historical grammar of the Ukrainian language. Key words: dialectology, lexicography, phraseology, dialectal speech, dialect, village Struhantsi. References